(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fluoride contamination in groundwater has emerged as a significant public health issue in various regions of India, including the state of Jharkhand. Fluoride contamination of groundwater in India has become a pressing public health issue. This contamination, stemming from natural and anthropogenic sources, has led to widespread fluorosis, affecting millions of individuals, particularly children. This paper provides an overview of the problem of fluoride contamination mainly in Jharkhand, India, highlighting its causes, consequences, and potential mitigation strategies. Fluoride contamination in Jharkhand primarily results from the geological composition of the region, where naturally occurring fluoride-rich rocks and minerals contribute to elevated levels of fluoride in groundwater. Consequently, many communities in the state are exposed to unsafe levels of fluoride through their drinking water sources, leading to adverse health effects such as dental fluorosis, skeletal fluorosis, and other related health problems. his paper also addresses the development of various methods for removing fluoride contamination.